Last Glacial Maximum – Holocene palaeoenvironment in Bessel Fjord and southwestern Dove Bugt, Northeast Greenland - Zoller, Kevin Michael (UiT Norges arktiske universitet, 2020)
Marine studies reconstructing ice sheet conditions on the Northeast Greenland shelf and adjacent fjords since the Last Glacial Maximum (LGM) are sparse. As a result, the timing and origin of the deglaciation of the ice sheet over marine areas is not well constrained. This thesis aims to improve our understanding of the LGM, deglaciation, and Holocene ice dynamics of the Greenland Ice Sheet (GrIS) near the southern outlet of the Northeast Greenland Ice Stream (NGIS), as well as reconstruct the palaeoenvironment of this region since the LGM. Here, swath bathymetry data and the multi-proxy analysis of three sediment gravity cores from southwestern Dove Bugt and Bessel Fjord were integrated. Dove Bugt is an embayment that is positioned to the east of Storstrømmen, the southern outlet of the NGIS. Bessel Fjord is a W-E oriented fjord that lies south of Storstrømmen and is connected to southern Dove Bugt via the Store Bælt sound. Bathymetric analysis of Dove Bugt revealed north-south oriented streamlined landforms which have been interpreted as the product of a fast-flowing, topographically bound branch of the NGIS that flowed southwards during the LGM. The sedimentology of a gravity core from southwestern Dove Bugt suggests that the NGIS may have retreat from the region around 11,190 cal. yr. BP, in conformity with previous onshore results. The presence of only a few, small retreat moraines implies that the deglaciation was rapid but may have had brief intervals of halting and/or readvancement. Sedimentation during the remainder of the Holocene is attributed to input from local ice caps and glaciers as well as mass wasting processes. The bathymetry of Bessel Fjord reveals several basins and sub-basin that are separated by basin thresholds. The configuration of geomorphic features suggests that glacial ice may have conformed to the topography during ice expansion and reached the outer fjord. The position of recessional moraines suggests that ice had undergone multiple halts and/or readvances and was topographically ...